Q: Y equals x3 plus 4x - 3.6?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

The answer to x4+x3-14x2+4x+6 divided by x-3 is x3+4x2-2x-2

(x + 2)(x^2+4)

64 is the cube of 4 so: x3 + 64 = (x + 4)(x2 - 4x + 16)

(x3 + 3x2 - 2x + 7)/(x + 1) = x2 + 2x - 4 + 11/(x + 1)(multiply x + 1 by x2, and subtract the product from the dividend)1. x2(x + 1) = x3 + x22. (x3 + 3x2 - 2x + 7) - (x3 + x2) = x3 + 3x2 - 2x + 7 - x3 - x2 = 2x2 - 2x + 7(multiply x + 1 by 2x, and subtract the product from 2x2 - 2x + 7)1. 2x(x + 1) = 2x2 + 2x2. (2x2 - 2x + 7) - (2x2 + 2x) = 2x2 - 2x + 7 - 2x2 - 2x = -4x + 7(multiply x + 1 by -4, and subtract the product from -4x + 7)1. -4(x + 1) = -4x - 42. -4x + 7 - (-4x - 4) = -4x + 7 + 4x + 4 = 11(remainder)

Suppose x3-4x = 0. To solve, factor: x3-4x = x(x2-4) = x(x+2)(x-2) = 0 Now, a product equals 0 if and only one or more of the factors equals 0, so set each factor to 0 and solve. The roots are 0,-2 and +2.

Related questions

x3 + x2 + 4x + 4 = (x2 + 4)(x + 1)

x^3+x^2+4x+4

The answer to x4+x3-14x2+4x+6 divided by x-3 is x3+4x2-2x-2

Dividend: 4x4-x3+17x2+11x+4 Divisor: 4x+3 Quotient: x3-x2+5x-1 Remainder: 7

Dividend: x3+4x2-9x-36 Divisor: x+3 Quotient: x2+x-12

x(x + 4)(x - 4) or x3 - 16x

x3 - 2x2 - 4x + 8 = (x2 - 4)(x - 2) = (x + 2)(x - 2)(x - 2)

(x + 2)(x^2+4)

x3+36 is an algebraic expression

[ x3 - 4x2 + 7x ] / (x) = x2 - 4x + 7

x3 + 6x2 - 4x - 24 = (x + 6)(x2 - 4) = (x + 6)(x + 2)(x - 2)

64 is the cube of 4 so: x3 + 64 = (x + 4)(x2 - 4x + 16)